Fifty Percent Size Reduction in Neuroendocrine Hepatic Metastasis After a Single Session of Trans-arterial Chemoembolization: A Case Report - Khassaf, Mustafa Saleem; Abed , Noor Yousif (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2025)
Background: The liver serves as a main site of metastatic disease, and cancer metastasis is considered the main limit to effectively managing the malignant tumors. NELM was found in 12% of people with gastrointestinal neuroendocrine neoplasms and 36% of people with pancreatic neuroendocrine neoplasms. Of those patients, 86% had liver-only metastases. Case description: On February 9, 2025, a 57-year-old male with neuroendocrine liver metastasis was admitted for transarterial chemoembolization (TACE) at Ibn Sina Interventional Radiology Center in Baghdad. The size of the hepatic lesions significantly decreased on follow-up imaging in June 2025, suggesting a successful course of treatment. TACE frequently calls for several sessions. The ideal number and frequency of sessions are still unknown, and repeating procedures can raise the risk of cumulative toxicity. Additionally, neuroendocrine liver metastases frequently display a variety of vascular patterns, which makes it more difficult to administer chemotherapy drugs consistently. In our case, both of these challenges are overcome; all lesions receive their blood supply from the superior mesenteric artery; replaced hepatic artery, and after the first session, there is a significant reduction in metastatic lesions, which undoubtedly delays the progression of the tumor and buys time before the next treatment is required. Usually, this results in a longer progression-free survival.